1994
DOI: 10.1177/088840649401700203
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Efficacy and the Instructional Practices of Special Education Teachers and Consultants

Abstract: ABSIRACT: The relationship between efficacy and selected instructional vareables was explored for two types of special education teachers. Teachers were categorized either as direct service providers, who provided direct instruction or behavioral interventions to students with mild disabilities, or as indirect service providers, who spent at least 50% of their time consulting, collaborating, or team teaching with general educators. Significant positive correlations found between efficacy and three instructiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
360
1
71

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(443 citation statements)
references
References 22 publications
11
360
1
71
Order By: Relevance
“…The second form of self-efficacy, referred to as inferred Researcher's Perception of Teacher's Self-Efficacy (RPTSE), required the development of an analytical framework informed by previous research study's descriptions of practice of teacher's identified as having high or low self-efficacy (for example, Allinder (1994) and Muijs & Reynolds (2001)). The analytical framework created consisted of four dimensions indicating teachers' levels of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The second form of self-efficacy, referred to as inferred Researcher's Perception of Teacher's Self-Efficacy (RPTSE), required the development of an analytical framework informed by previous research study's descriptions of practice of teacher's identified as having high or low self-efficacy (for example, Allinder (1994) and Muijs & Reynolds (2001)). The analytical framework created consisted of four dimensions indicating teachers' levels of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to be less critical of students who make errors (Ashton and Webb, 1986), spend more time with students who are struggling (Gibson and Dembo, 1984) and tend to exhibit greater levels of planning and organization (Milner, 2001). They are committed (Colodarci, 1992) and will stay in this profession longer (Milner, 2002;Allinder, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There are many other benefits in being highly efficacious. Teachers with a high sense of efficacy exhibit greater enthusiasm in teaching (Allinder, 1994;Hall et al, 1992). They tend to be less critical of students who make errors (Ashton and Webb, 1986), spend more time with students who are struggling (Gibson and Dembo, 1984) and tend to exhibit greater levels of planning and organization (Milner, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers categorised to have 'high teacher self-efficacy' have been observed to demonstrate the following attributes and/or pedagogical practices, including: good subject knowledge (Riggs 1995;Ross 1998;Muijs & Reynolds 2002;Cantrell, Young & Moore 2003); high levels of planning, organization and enthusiasm (Allinder 1994;Muijs & Reynolds 2002); and a willingness to experiment with new teaching methods, persisting even if initial implementation is flawed (Haney, Czerniak & Lumpe 1996;Cousins & Walker 2000). Furthermore, teachers who are reported to have high teacher self-efficacy use a variety of teaching methods (Cantrell & Callaway 2008), are less reliant on curriculum guides and emphasise cross-curriculum links during teaching (De Laat & Watters 1995).…”
Section: Understanding Self-efficacymentioning
confidence: 99%
“…In the Literature Review, we listed teacher characteristics associated with high teacher self-efficacy. For example, high levels of planning, organization and enthusiasm (Allinder 1994;Muijs & Reynolds 2002) and a willingness to experiment with new teaching methods and persist if initial implementation was flawed (Haney et al 1996;Cousins & Walker 2000). The second stage was to organise and group the attributes and practices.…”
Section: Qualitative Analysismentioning
confidence: 99%